Selecting a technical service provider by using the analytic hierarchy process - Riyadi, slamet; Effendi, Lokman; Islam, Rafikul (Malaysian Institute of Management, 2013)
A bidding to select a suitable technical service provider at the oil and gas industry could be a lengthy process. The analytic hierarchy process (AHP) method is proposed in order to identify the best technical service provider to perform a field development plan (FDP) document of Field X. This method is expected to be able to expedite the procurement process. In AHP analysis, the Technology Capability and the Project Deliverability criteria receive the highest overall weights, 0.270 and 0.244, respectively, while Reliability Company and Technology Transfer have lower similar weights, 0.067 and 0.069, respectively. The Cost criterion is the third highest, and the Track Record Performance criterion is the fourth highest in terms of importance, their weights are, 0.188 and 0.162, respectively. The Provider 5 and Provider 1 have the highest and the second highest overall weights, which are 0.2895 and 0.2546 respectively, while the Provider 2 has the lowest overall weight, 0.1246. Finally, based on this method, the Provider 5 is selected as the provider to conduct the works of developing FDP for the Field X.